Annual Reviewer Acknowledgement - Oladipo Ojo, Dr. Emmanuel (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
The Editorial team of the journal would like to thank the reviewers for their work in refereeing manuscripts during 2019